Defesas contra herbivoria no cerrado: síndromes de defesa e originalidades - Silva, Danilo Muniz da (Universidade Federal de São Carlos, 2010)
Plants have traits against herbivory that may occur together and increase defense efficiency. We tested whether there are defense syndromes in a cerrado community and, if so, whether there is a phylogenetic signal in them. We measured nine defense traits from a woodland cerrado community in southeastern Brazil. We tested the correlation between all pairs of traits and grouped the species into defense syndromes according to their traits. Most pairwise correlations of traits were complementary. Plants with lower specific leaf area also presented tougher leaves, with low nitrogen, more trichomes, and tannins. We found five syndromes: two with low defenses and high nutritional quality, two with high defenses and low nutritional quality, and one with traits compensating each other. There were two predominant strategies against herbivory in cerrado: tolerance and low nutritional quality syndromes. Phylogeny was not determining the suite of traits species presented; so, herbivory could be regarded as a biotic factor selecting these traits. Complementarity allows species coexistence and more efficient use of niche. Originality of a species is how much that species contributes to rarity of traits. Here we (1) tested the relation between abundance and both phylogenetic and phenotypic originalities and (2) compared abundance-based extinctions to random ones. We measured nine defense traits, phylogenetic information and abundance from a woodland cerrado community in southeastern Brazil. Abundance was not related to neither phylogenetic nor functional originalities; phylogenetic and phenotypic originalities were not related. Abundance-based extinctions were not different from random. However, the originalities were concentred in few species and four of the more original species were among the rarest. These species contribute to rarity of traits more than common ones and they may contribute to compensatory dynamics and to maintenance of community stability. Thus, species abundance may not be a predominant factor to the maintenance of functions in cerrado.
Keywords: Ecologia vegetal; Extinção (Biologia); Filogenia; Herbivoria; Síndromes; CIENCIAS BIOLOGICAS::ECOLOGIA